Super-resolution binding activated localization microscopy through reversible change of DNA conformation. (31st December 2018) - Szczurek, Aleksander; Birk, Udo; Knecht, Hans; Dobrucki, Jurek; Mai, Sabine; Cremer, Christoph
ABSTRACT: Methods of super-resolving light microscopy (SRM) have found an exponentially growing range of applications in cell biology, including nuclear structure analyses. Recent developments have proven that Single Molecule Localization Microscopy (SMLM), a type of SRM, is particularly useful for enhanced spatial analysis of the cell nucleus due to its highest resolving capability combined with very specific fluorescent labeling. In this commentary we offer a brief review of the latest methodological development in the field of SMLM of chromatin designated DNA Structure Fluctuation Assisted Binding Activated Localization Microscopy (abbreviated as fBALM) as well as its potential future applications in biology and medicine.